The Influence of Influencer Marketing on Brand Awareness of Gadget Products among TikTok Users in Indonesia - Bintang Arya Yudha W; Marchyel Mahardika W; Dina Kartini (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the influence of influencer marketing on brand awareness of gadget products among TikTok users in Indonesia through a qualitative systematic literature review approach. Drawing on seven empirical studies published between 2021 and 2026, this research synthesizes findings on how influencer marketing analyzed through the lens of Source Credibility Theory shapes consumer brand awareness and purchase intention in the context of digital technology products. The findings indicate that influencer credibility, comprising trustworthiness, expertise, and attractiveness, is the primary driver of brand awareness formation, with influencer credibility explaining up to 27.0% of variance in purchase intention (Istimaroh, 2025) and influencer marketing explaining 49.7% of variance in purchase intention for gadget products (Maesaroh, 2025). TikTok-specific studies confirm that influencer content on the platform contributes to sales performance increases of 25–30% for brands (Sakir, 2025), while brand awareness consistently emerges as a critical mediating variable between influencer marketing activities and consumer behavioral outcomes. The study further identifies that the authenticity of influencer content and the quality of parasocial relationships between influencers and their audiences are key determinants of the effectiveness of influencer marketing campaigns in building gadget brand awareness. This study concludes that a credibility-centered influencer marketing strategy represents the most sustainable approach for gadget brands seeking to build meaningful brand awareness among Indonesian TikTok users.